A review of the immunopathogenesis of Brucellosis. Issue 5 (4th May 2019) - Amjadi, Omolbanin; Rafiei, Alireza; Mardani, Masoud; Zafari, Parisa; Zarifian, Ahmadreza
Abstract: Brucellosis, caused by the intracellular pathogens Brucella, is one of the major zoonotic infections. Considering the economic burden, its prevalence has been a health concern especially in endemic regions. Brucella is able to survive and replicate within host cells by expressing different virulence factors and using various strategies to avoid the host's immune response. This leads to progression of the disease from an acute phase to chronic brucellosis. Exploration of genetic variations has confirmed the expected influence of gene polymorphisms on susceptibility and resistance to brucellosis of humans. Since there is no approved human vaccine and treatment is uncertain with risk of relapse, it is important to increase knowledge about pathogenesis, diagnosis and treatment of brucellosis in order to manage and control this infection, especially in endemic regions.